Impact California Social studies - United States history & geography continuity & change - Appleby, Joyce Oldham; Brinkley, Alan; Broussard, Albert S.; McPherson, James M.; Ritchie, Donald A. (McGraw-Hill Education, 2019)
[TE. 1] Teacher's edition -- [TR. 1] Project-based learning -- [WB. 1] Inquiry journal.